A Closer Look at the Interactive Screening Program (ISP): Trends in Usage of an Online Screening Program. Issue 1 (2nd January 2021) - Daltry, Rachel; Sibley, Stephanie; MacNamara, Luciana
ABSTRACT: The purpose of this study was to analyze trends in the utilization of the Interactive Screening Program (ISP) with a population of students attending a college in the northeast. By making note of specific patterns and observations in the current usage of ISP among this population, it is believed that ISP's potential usefulness for other college campuses and any existing barriers to seeking mental health treatment among college students might be better understood. It was found that there was no significant difference in submissions based on time of day or week. Thus, roughly the same number of students submitted questionnaires during the normal operational hours of the counseling center and during nights and weekends when the counseling center was closed. It is believed that the ability to receive brief clinical feedback, learn more about counseling services, and dialogue directly with counselors all through an anonymous, online portal represents a more comfortable way for some students to connect to mental health services.